Penyuluhan Dan Pelatihan Kesehatan Gigi Sebagai Deteksi Karies Gigi Anak Di Desa Sukaramai Dua Aceh Tamiang - Pandia, Ekariana S.; Indriaty; Tri Mustika Sarjani (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Oral health is one of the impacts that affect children's development in brain development, one of the oral health is dental health, dental health awareness needs to be reviewed from the environmental, educational, and public awareness aspects with treatment and prevention. These aspects are interrelated and influence each other, prevention and dental care of the community, especially children. Dental caries can be prevented early if there is participation from the family and the surrounding environment of Sukaramai Dua Village, which is a village in Aceh Tamiang, has a population of 2,776 with 820 active school children and 540 children under 7 years old. Among them have problems with oral health, especially dental problems. Based on the problems faced by partners, the Community Service team offers solutions, namely (1) Conducting counseling to Sukaramai Dua Community partners on the importance of maintaining dental health, especially for preschool children (2) Providing training to preschool children in cleaning their teeth properly. The method of implementing activities includes three main stages, namely field surveys, stage two socialization, stage three training. It is hoped that there will be an increase in knowledge and awareness of oral health, especially dental health which affects brain development in preschool children in Sukaramai Dua Village, Aceh Tamiang.